Incidental Hyperferritinemia in Very Young Infants with Mild Symptoms of COVID-19 Disease - Yuka Shishido; Haruhiko Nakamura; Tomohiro Nakagawa; Shinsuke Kanou; Takeshi Ito; Shota Kuwana; Chiharu Ota (MDPI AG, 2023)
Background: The number of children infected with novel coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has increased during the outbreak of the Omicron strain. Hyperferritinemia has been reported in severe cases of COVID-19, and in children or neonates with multisystem inflammatory syndrome (MIS). Hyperferritinemia is considered to be one of the signs of MIS, but thus far, there have been few summarized reports on it. We retrospectively analyzed four infants less than 3 months of age with SARS-CoV-2 infections treated in our institution during the outbreak of the Omicron strain. Results: most patients were in good condition, but hyperferritinemia was observed in all of four cases. Conclusions: Hyperferritinemia can be observed in infantile COVID-19 patients even with mild symptoms. It is necessary to carefully monitor their clinical course and monitor the patients.